Time-varying intensity of oxygen exposure is associated with mortality in critically ill patients with mechanical ventilation - Zhu Zhu; Mingqin Zhou; Yao Wei; Hui Chen (Critical Care, 2022)
Abstract Background There is no consensus exists regarding the association between oxygen exposure (arterial oxygen tension or fraction of inspired oxygen) and outcomes for patients with mechanical ventilation. Additionally, whether the association remains persistent over time is unknown. We aimed to explore the association between exposure to different intensities of oxygen exposure over time and 28-day mortality in patients with mechanical ventilation. Methods We obtained data from the Medical Information Mart for Intensive Care IV (MIMIC-IV), which included adult (≥ 18 years) patients who received invasive mechanical ventilation for at least 48 h. We excluded patients who received extracorporeal membrane oxygenation (ECMO) or who initiated ventilation more than 24 h after ICU admission. The primary outcome was 28-day mortality. Piece-wise exponential additive mixed models were employed to estimate the strength of associations over time. Results A total of 7784 patients were included in the final analysis. Patients had a median duration of invasive mechanical ventilation of 8.1 days (IQR: 3.8–28 days), and the overall 28-day mortality rate was 26.3%. After adjustment for baseline and time-dependent confounders, both daily time-weighted average (TWA) arterial oxygen tension (PaO2) and fraction of inspired oxygen (FiO2) were associated with increased 28-day mortality, and the strength of the association manifested predominantly in the early-middle course of illness. A significant increase in the hazard of death was found to be associated with daily exposure to TWA-PaO2 ≥ 120 mmHg (Hazard ratio 1.166, 95% CI 1.059–1.284) or TWA-FiO2 ≥ 0.5 (Hazard ratio 1.496, 95% CI 1.363–1.641) during the entire course. A cumulative effect of harmful exposure (TWA-PaO2 ≥ 120 mmHg or TWA-FiO2 ≥ 0.5) was also observed. Conclusion PaO2 and FiO2 should be carefully monitored in patients with mechanical ventilation, especially during the early-middle course after ICU admission. Cumulative exposure to higher intensities of oxygen exposure was associated with an increased risk of death.